HARMONISASI HUKUM PENGELOLAAN PENDIDIKAN TINGGI KREATIF MEDIA UNTUK PENGEMBANGAN INDUSTRI KREATIF - RR Ella Evrita H, S.E, M.M, RR Ella Evrita H, S.E, M.M (Akademi Komunikasi SAE Indonesia, 2023)
The development of the Creative industry in Indonesia has made great progress both in terms of the achievements of people, works and creative businesses in Indonesia. This achievement means that the Creative Industry in Indonesia has the potential to continue to be developed. In addition to potential, there are also constraints with existing problems, the availability of creative, professional, and competitive resources. This can be improved by two aspects, namely Education and Capacity Building for creative workers. In addition, the development of creative industries affects interests and hobbies as well as new knowledge that will give rise to new types of education, which in this case is in accordance with Law No. 20 of 2003 concerning the National Education System Article 1 General Provisions Paragraph 2